The impact of work stress on the job dropout of human resources: An exploratory study in the ministry of trade the general company for foodstuff trade in iraq – baghdad (Entrepreneurship Journal for Finance and Business, 2022)
The research aimed to identify the level of influence of work stress on the job dropout of human resources, In the General Company for Foodstuff Trade, one of the formations of the Ministry of Trade in Baghdad - Iraq, The descriptive-analytical method was used to complete the stages of scientific research. The researcher also used the questionnaire as a tool to measure the level of influence between the research variables. Where (65) questionnaires were distributed to the research sample, Sixty-three (63) questionnaires were subjected to statistical analysis. The researcher used and applied (SPSS:V-24) and (Excel:V-2013) and some scientific statistical methods. approved in the analysis and interpretation of the answers of the target sample, The research came to a number of conclusions, The most important of them was that the company’s employees suffer from job stress as follows: Role ambiguity, working conditions, role conflict, workload, In addition to the existence of a statistically significant effect of work pressures on the job dropout of human resources in the company under study, The researcher also recommended the necessity of seeking the advice of experts, specialists and professors of Iraqi universities. In the field of human resource management and organizational behavior, In order to develop strategic plans that reduce the severity of the work pressures that may occur in the future for the company’s employees and alleviate their suffering, and thus reduce their job dropout rate. In addition to adopting the conclusions and recommendations of the research, in order to address the work pressures of all kinds and sources, to reduce the rate of job dropout among the human resources working in the company above.